4D Printing of Magnetic Shape Memory Alloys - Milleret, Anastassia (Cranfield University, 2020)
Magnetic shape memory alloys (MSMA) are ferromagnetic materials exhibiting a plastic reversible transformation. Compared to thermally activated shape memory alloys, such as NiTi, the response of MSMA is much faster (less than a millisecond), making them good candidates for actuators, sensors, micro pumps and energy harvesters. To date, the Ni-Mn-Ga system is the most studied MSMA, and is the focus of this study. The shape memory effect in MSMA is driven by a phase transformation from a high ordered austenitic Heusler phase to a lower symmetry martensitic phase. The change in the shape occurs within the martensitic phase in the presence of a magnetic field. This is due to the reorientation of the twin variants. The best magnetic shape memory effect was reported in single crystalline Ni-Mn-Ga exhibiting up to 10% strain. However, in the polycrystalline form, grain boundaries create obstacles for twin boundary motion and thus the shape memory effect is reduced. Nevertheless, recent studies show a high magnetic-field induced strain, up to 8.7%, in polycrystalline Ni-Mn-Ga foams. Increasing porosity and grain size decreases the grain boundary constraint. MSMAs foams can be made using ceramic space holders, by binder-jetting or by ink-printing. However, these techniques create random distribution and/or size porosity. Further investigations are required to control porosity and grain morphology to enhance the shape memory effect. In addition, magnetic properties are orientation-dependant. Previous studies have reported the possibility to control the grain orientation via laser-powder bed fusion (l-PBF) additive manufacturing technique by tuning the printing parameters and the scanning strategy. Thus, l-PBF appears to be a potential approach to create near-net shape oligocrystalline and foam-structure Ni-Mn-Ga.
Keywords: 'DSDS20 3MT'; 'DSDS20'; 'Magnetic Shape Memory Materials'; 'Laser Powder Bed Fusion'; 'Additive Manufacturing'; 'Additive Manufacturing'